Study on relationship between maternal haemoglobin and the early neonatal outcome in term babies - Paramahamsa, R. Rama Krishna; Chakravarthi, G. Kalyan (International Journal of Contemporary Pediatrics, 2019)
Background: Iron stores of neonates born to anaemic mothers are low, iron content in breast milk in anaemic women is low and because of these factors substantial proportion of infants become anaemic by six months. Thus maternal iron deficiency and anaemia makes the offspring vulnerable for developing iron deficiency anaemia right from infancy. The current study was made attempt to evaluate and establish the relationship between maternal haemoglobin and early neonatal outcome in term babies. Method: The present cross-sectional observational study conducted in term neonates and their mothers in first stage of labour in the Department of Paediatric and Department of Obstetrics & Gynaecology, GSL Medical College and general hospital, Rajamahendravaram, from 2015 to 2017. Relevant history of mother was recorded and blood sample from the mother was collected in first stage of labour for haemoglobin estimation. Result: The mean haemoglobin in anaemic mothers was found to be 9.48±0.413 gm/dl and that in non-anaemic mothers was 11.67±0.515gm/dl. Anaemia among mothers has significant effect on birth weight of the newborn babies, on crown heel length of the newborn babies (P<0.05) and on head circumference of Newborn babies (P< 0.05). It was found that anaemia among mothers has no significant effect on APGAR score at 5 mins and on hospital stay. Conclusion: Anaemic mothers had newborn with low mean birth weight, low mean head circumference and low crown heel length compared to the those of non anaemic mothers.